ANALYSIS OF TIME MANAGEMENT IN ONLINE LEARNING AT DARUZ ZAHRA ISLAMIC BOARDING SCHOOL - Akhmad Syahri (Jurnal Tatsqif, 2021)
This study aims to determine the effectiveness of time management in bold learning at Daruz Zahra Islamic Boarding School. Students who live in Islamic boarding schools and participate in formal school activities are based on their knowledge of time. However, are students able to manage the time to study materials at Islamic boarding schools and general studies at school during the Covid-19 pandemic? Researchers used descriptive qualitative research methods with data collection techniques and a semi-structured interview model in the form of a questionnaire distributed to 7 students. The data obtained was then processed by tabulating the answer data, description and analysis, data synthesis, and discussion. The results showed that: 1) continuous learning for Daruz Zahra Islamic Boarding School students was not very effective. This was caused by repeated boredom, so that it reached a saturation point. 2) Less than half of the material that students can absorb, coupled with the ability of teachers and students to use the internet, is still low, 3) Students tend to find it difficult to manage their time between formal learning and studying in Islamic boarding schools. Therefore, courageous learning should ideally be carried out in certain conditions and times that do not allow face-to-face meetings, such as natural disasters, and accompanied by increased professionalism of educators in using technology so that learning is not boring.